The Dark Bride: A Date In La Catunga (2007)
This paper analyzes The Dark Bride, a novel written by the Colombian writer Laura Restrepo. It develops a reflection on the history and life in Tora and in the Middle Magdalena region during the first half of the twentieth century, when oil companies firs